Responsiveness of objective, disease-specific, and generic outcome measures in patients with chronic low back pain: an assessment for improving, stable, and deteriorating patients. - Campbell, H; Rivero-Arias, O; Johnston, K; Gray, A; Fairbank, J; Frost, H (2006)
STUDY DESIGN: Analysis of outcome data collected prospectively from 250 patients recruited to the UK Spine Stabilization Trial. OBJECTIVES: To compare the responsiveness of the Shuttle Walking Test (SWT), which is an objective outcome measure, with that of a disease-specific (the Oswestry Disability Index) and 2 generic (the EQ-5D and SF-36) instruments in patients with chronic low back pain (LBP). SUMMARY OF BACKGROUND DATA: Studies assessing the performance of subjective disease-specific and generic measures have increased in recent years, although there is a paucity of research reporting the responsiveness of objective measures in patients with LBP. The focus of investigation has been on responsiveness to improvements in LBP symptoms. For patients with deteriorating health, it remains largely unclear how outcome instruments perform. METHODS: Baseline and 12-month outcome data collected on 250 patients with chronic LBP recruited to the Spine Stabilization Trial were analyzed using traditional measures of responsiveness. Analyses were performed for 3 groups of patients: those who rated their health status as improved, deteriorated, and stable at 12 months. RESULTS: The SWT was shown by all measures to be responsive to health improvement, although less so than other instruments. All instruments were able to detect small-to-moderate reductions in health. Instrument floor effects may be responsible for small SF-36 change scores recorded for deteriorating patients. CONCLUSIONS: Although shown to be responsive, including the SWT alongside disease-specific and generic instruments is unlikely to add additional information. All instruments appear responsive to patient deterioration, however, further research for the SF-36 is required.